Evaluating the Efficacy and Safety of Direct Oral Anticoagulants Compared to Vitamin K Antagonists in Patients with Antiphospholipid Syndrome: Updated Systematic Review and Meta-Analysis - Lama Alfehaid PharmD, MME; Nada Alsuhebany PharmD; Hussah Albahlal PharmD; Albatoul Alomran PharmD; Abdulmajeed M Alshehri PharmD; Mohammed AlSheef MD; Abdulaali Almutairi PharmD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Background Antiphospholipid Syndrome (APS) is an autoimmune condition that increases thrombosis risk. Although Vitamin K antagonists (VKA) are standard treatment, interest in direct oral anticoagulants (DOAC) has grown. Recent studies evaluated DOAC across all APS subgroups. This review updates our understanding of DOAC's efficacy and safety compared to VKA in preventing thrombotic complications, integrating new findings into the literature. Methods A systematic review across PubMed/Medline, Embase, and Cochrane was conducted in accordance with PRISMA guidelines. The quality of randomized controlled trials (RCTs) and cohort studies was assessed using the Cochrane Risk of Bias tool and the Newcastle-Ottawa Scale, respectively. Meta-analysis calculated odds ratios (OR) using the random effect model for arterial and venous thrombotic and bleeding outcomes Results Of a total of 2385 records identified, the meta-analysis included 11 studies, comprising 5 RCTs and 7 observational studies, with a combined total of 1813 participants. The analysis revealed no significant difference in the odds of venous thromboembolism (VTE) between DOAC and VKA (OR = 0.80; 95% CI 0.41-1.56). However, a significant increase in thromboembolism recurrence was noted in triple-positive APS patients using DOAC compared to VKA (OR = 3.62; 95% CI 1.10-11.98). The risk of major bleeding was similar between DOAC and VKA (OR = 1.02; 95% CI 0.62-1.68). Additionally, the pooled analysis indicated a higher risk of arterial thrombosis with DOAC (OR = 6.21; 95% CI 2.06-18.76). Conclusion Overall, findings suggest DOAC are comparably safe but increase the risk of arterial thrombosis and VTE in triple-positive APS, favoring warfarin for prophylaxis.